Hierarchy of contamination control in the fire service: Review of exposure control options to reduce cancer risk. Issue 9 (2nd September 2022) - Horn, Gavin P.; Fent, Kenneth W.; Kerber, Steve; Smith, Denise L.
Abstract: The international fire service community is actively engaged in a wide range of activities focused on development, testing, and implementation of effective approaches to reduce exposure to contaminants and the related cancer risk. However, these activities are often viewed independent of each other and in the absence of the larger overall effort of occupational health risk mitigation. This narrative review synthesizes the current research on fire service contamination control in the context of the National Institute for Occupational Safety and Health (NIOSH) Hierarchy of Controls, a framework that supports decision making around implementing feasible and effective control solutions in occupational settings. Using this approach, we identify evidence-based measures that have been investigated and that can be implemented to protect firefighters during an emergency response, in the fire apparatus and at the fire station, and identify several knowledge gaps that remain. While a great deal of research and development has been focused on improving personal protective equipment for the various risks faced by the fire service, these measures are considered less effective. Administrative and engineering controls that can be used during and after the firefight have also received increased research interest in recent years. However, less research and development have been focused on higher level control measures such as engineering, substitution, and elimination, which may be the most effective, but are challenging to implement. A comprehensive approach that considers each level of control and how it can be implemented, and that is mindful of the need to balance contamination risk reduction against the fire service mission to save lives and protect property, is likely to be the most effective.